Morphofunctional changes of sterno-costal junctions of Experimental Diabetes mellitus (Multidisciplinary Journal of Science and Technology, 2023)
Diabetes mellitus is on the list of social problems and is accompanied by profound changes in the human body. Disturbances of peripheral microcirculation and innervation are observed with a long course of the disease . The morphofunctional active point in the formation of the chest is the sternocostal complex. Changes in the shape and functional structure of the chest affect the functional state of the chest cavity organs.